(untitled) (Journal of Economic Research & Business Administration, 2017)
Creation of the Eurasian Economic Union and its work influences the economic growth of the country. Mutual trade between the states of EEU depends on a number of factors. It means that in EEU building-up of a mutual goods turnover of state members of the union and carrying out measures for stabilization of a situation are necessary in coordination of macroeconomic policy. Besides, the synergetic effect of integration and EEU is possible only in the case of implementation of integration potential of mutual trade. The purpose of economic union creation is to increase an export volume of policy, integrational relations and economic development, and for the purpose of expanding of work it represents great opportunities for improving welfare of the population. Due to creation of economic union, every state can maximally promote the economic feasibilities. Countries-partners have comfort terms for the improvement of quality of products, modernisation of production and technologies, development of a transport infrastructure. Methodical bases of research of regional integration structures, as groups from a number anchorwomen in outer space of union of subjects, pre-conditions and factors, influencing on the height of economy, are examined in that.